VALIDASI METODE ANALISIS KADAR AMBROKSOL HIDROKLORIDA DALAM SEDIAAN TABLET CYSTELIS SECARA KROMATOGRAFI CAIR KINERJA TINGGI - Ade Heri Mulyati; - Sutanto; Dewi Apriyani (EKOLOGIA, 2011)
Cystelis tablet is an expectorant medicine which contain 30 mg/tablet of Ambroxol Hydrochloride. To ensure the safety and effectiveness of the medicine must be well controlled especially the analytical methode which used to determined the actived ingredient in the medicine. This analytical methode must resulting the amount of Ambroxol Hydrochloride which can be trusted. The purpose of this research are to test and proof the result of determination Ambroxol Hydrochloride in Cystelis tablet could be trusted in daily test in laboratorium. Analytical methode validation is a effort to get and documented proof that the result of test methode can be trusted with some specification. The Parameters of analytical methode validation are precision, linearity, accuracy, range, selectivity, and stability test (robustness). Analytical methode that used in pharmacy specially High Performance Liquid Chromatography (HPLC), using mobile phase metanol : buffer potassium dyhidrogen phosphate 0,01 M (70:30) pH 6,0 and stationary phase C18 Symmetry (150 mm x 4,6 mm) with particle size 5mm, flow rate 1,0 mL/minute, injection volume 10,0 mL and measured at wavelength 247 nm. Analytical results showed that the placebo did not gived any analytical respons in selectivity test. Accuracy which know as % recovery showed the average of % recovery 99,31% (98,70 100,44%), range between 80%-120%. Linearity at consentration range 70% - 130% with coefficient correlacy (r) 0,99924. The result of precision which is repeatability with average of % RSD 0,25%. Based on t value and F value on intermediate precision showed that there is no differently result gived by the analytical methode with different analyst and time. Stability test solution and mobile phase composition with % bias 2% and %RSD 2%. Based on the analytical methode validation result the determination of Ambroxol Hydrochloride in Cystelis tablet with high performace liquid chromatography we can conclude that this analytical methode is valid to implemented in daily inspection at Quality Control laboratory PT. Armoxindo FarmaKata kunci : Validation, Analytical methode, Ambroxol Hydrochloride, HPLC